Media Permainan Busy Board Untuk Menstimulasi Motorik Halus Anak - Theresia, Theresia; Sutrisno, Sutrisno; Yuniarti, Yuniarti (PrimEarly : Jurnal Kajian Pendidikan Dasar dan Anak Usia Dini, 2024)
This study aims to examine and understand the Busy Board game media to stimulate fine motor skills of children aged 5-6 years at PAUD KB Mandiri Paoh Concong Village, Ketapang. The research method used is an experiment with a quantitative approach. The data sample of this research is children aged 5-6 years in class B, totaling 13 children. Data sources were obtained based on test results (pretest and post-test) and observation of child development in the classroom. The results revealed that the validation of material experts obtained a value of 100% with the category “Very Feasible”. Media expert validation obtained a value of 75% with the category “Worth Using”. The results of stage I observations obtained an average value of 25.7 (64.25%) with the category “Developing as expected”. Phase II observations have increased, obtained an average value of 38.95 (94.5%) in the “Developing Very Well” category. Thus it is concluded that Busy Board media can be used in the learning process in the classroom at KB Mandiri PAUD.